2023
DOI: 10.21123/bsj.2023.8394
|View full text |Cite
|
Sign up to set email alerts
|

Traveling Wave Solutions of Fractional Differential Equations Arising in Warm Plasma

Abstract: This paper aims to study the fractional differential systems arising in warm plasma, which exhibits traveling wave-type solutions. Time-fractional Korteweg-De Vries (KdV) and time-fractional Kawahara equations are used to analyze cold collision-free plasma, which exhibits magnet-acoustic waves and shock wave formation respectively. The decomposition method is used to solve the proposed equations. Also, the convergence and uniqueness of the obtained solution are discussed. To illuminate the effectiveness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It is observed that, most of the models are developed by using ordinary and partial derivatives, which means that they are free from the memory effect. In the last two decades, fractional differential equations (FDEs) have been widely used in the modeling of real life problems [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that, most of the models are developed by using ordinary and partial derivatives, which means that they are free from the memory effect. In the last two decades, fractional differential equations (FDEs) have been widely used in the modeling of real life problems [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%